Giant Bullous Emphysema With Placental Transmogrification: A Case Report of a 14-Year-Old With Right Middle- and Lower-Lobe Involvement. (December 2017) - Lowenthal, Brett M.; Saenz, Nicholas C.; Lin, Grace Y.; Newbury, Robert O.
Giant bullous emphysema with placental transmogrification is an extremely rare entity, with 30 previously reported cases. Of these reported cases, it is typically identified with varied clinical and radiological impressions, presents in young adulthood to elderly, is always unilateral, and usually involves just one lobe. Despite the unknown pathogenesis, this diagnosis carries an excellent prognosis and is curative with complete resection. The pulmonary placental transmogrification is histologically indistinguishable from placental origin. Although not necessary to utilize because of the male predominance and no reported association, immunohistochemical stains can be used to prove lung origin. We report an extremely rare case of 2-lobe involvement of giant bullous emphysema with placental transmogrification in a boy 14 years of age, who is the youngest diagnosed patient with this lung abnormality.